Simultaneous Tyrosine and Serine Phosphorylation of STAT3 Transcription Factor Is Involved in Rho A GTPase Oncogenic Transformation - Aznar, Salvador (The American Society for Cell Biology, 2001)
Stats (signal transducers and activators of transcription) are latent cytoplasmic transcription factors that on a specific stimulus migrate to the nucleus and exert their transcriptional activity. Here we report a novel signaling pathway whereby RhoA can efficiently modulate Stat3 transcriptional activity by inducing its simultaneous tyrosine and serine phosphorylation. Tyrosine phosphorylation is exerted via a member of the Src family of kinases (SrcFK) and JAK2, whereas the JNK pathway mediates serine phosphorylation. Furthermore, cooperation of both tyrosine as well as serine phosphorylation is necessary for full activation of Stat3. Induction of Stat3 activity depends on the effector domain of RhoA and correlates with induction of both Src Kinase-related and JNK activities. Activation of Stat3 has biological implications. Coexpression of an oncogenic version of RhoA along with the wild-type, nontransforming Stat3 gene, significantly enhances its oncogenic activity on human HEK cells, suggesting that Stat3 is an essential component of RhoA-mediated transformation. In keeping with this, dominant negative Stat3 mutants or inhibition of its tyrosine or serine phosphorylation completely abrogate RhoA oncogenic potential. Taken together, these results indicate that Stat3 is an important player in RhoA-mediated oncogenic transformation, which requires simultaneous phosphorylation at both tyrosine and serine residues by specific signaling events triggered by RhoA effectors.